Lazer Kaynak Dikişi Geometrisinin Cevap Yüzeyi Metodu (rsm) İle Optimizasyonu - Bozan, Aslı (Fen Bilimleri Enstitüsü, 2013)
girdi değerlerinin değiştirilmesiyle elde edilebilecek olan çıktı (derinlik, kalınlık ve genişlik) değerlerinin nasıl değişeceğini gözlemleyebilmek ve istenilen toleranslarda kaynak bölgesi sağlayabilmek için girdilerin aralarındaki ilişkiyi görmek amaçlı yapılmıştır. Farklı iki girdi parametresi, farklı iki kolimasyon cihazı için, ayrı ayrı değiştirilerek denemeler yapılmıştır. Lazer kaynak prosesini etkileyen birçok önemli parametreler (vakum, lazer ışın kalitesi, lazer ışın iz düşümü, ortamın steril olması... vs.) bulunmaktadır. Bunların arasından kaynak kalitesine en çok etken olduğu bilinen- tecrübe ve önceki çalışmalar sonucunda- lazer gücü ve kaynak hızı girdi parametreleri olarak belirlenmiştir.

This study focuses on the development of mathematical models for selection of process parameters and the prediction of weld seam geometry in Nd:YAG laser welding. Factorial design can be employed as a guide for optimization of process parameters. Welding input parameters play a significant role in determining the quality of weld seam geometry. Two factors for two different collimations were incorporated into the factorial model; laser power and welding speed. The RSM results shows that developed mathematical models can be applied to estimate the effectiveness of process parameters for a given seem geometry (width,depth, thickness) and indicate optimum inputs values for a good welding quality. At the end of this study, response surface optimizer was used for finding the best conformity of the input (laser welding and welding speed) parameters that were found from the output tolerances which means the suitable laser welding seam geometry. The values, which were occured from the response surface optimizer, were tried on the laser welding process bench and all output parameters (width,depth, thickness) were conform.The conformation of the this study indicates that the study is real-like and achieved it’s objective.
Optimization Of Laser Welding Seam Geometry Using Response Surface Methodology (rsm)
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: DOE; yüzey cevap metodu; lazer kaynak; kaynak geometrisi; modelleme; modelling